Evaluating the robustness of nature-based solutions: future resilience of sedum-based soft capping as a conservation approach for heritage sites in Britain and Ireland - Richards, J; Cooke, EL; Coombes, M; Jones, J; Viles, H (Taylor and Francis, 2023)
Nature-based solutions are seen to benefit both society and biodiversity. However, research into their future resilience is required. Soft capping is a nature-based conservation strategy that mimics the natural colonisation of plants on top of ruined walls and reduces rates of material deterioration. To remain effective, soft capping species must be tolerant of future climatic conditions. We use the Maxent species distribution model to assess the resilience of soft capping species to low and high emission scenarios across Britain and Ireland. We assess the mid- and end-century presence probability of four native and archaeophyte species used in soft capping (Sedum album, S. acre, S. anglicum and Saxifraga granulata). Future presence probabilities were calculated using the climate models HadGEM3-GC31-LL, IPSL-CM6A-LR and MIROC6. Results suggest that current sedum-based soft caps will remain viable until mid-century with additional maintenance (e.g. watering) during droughts, although soft caps predominantly formed of Sedum album may be prone to failure in south-eastern England. In the future, species more resilient to arid conditions may need to be preferentially selected for soft capping to ensure resilience under a warming climate. Species distribution modelling provides a useful way of predicting the future resilience of nature-based solutions.